PENINGKATAN KOMPETENSI HOMILETIKA BAGI PENGKHOTBAH DAN CALON PENGKHOTBAH GBI MIRACLE SERVICE AUSTRALIA MELALUI PROGRAM TRAINING TERSTRUKTUR - Apin Militia Christi; Yoel Betakore; Heru Cahyono (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2026)
This community service program aimed to improve the homiletical competence of preachers and prospective preachers at GBI Miracle Service Australia through a structured training program. The activity was conducted online via Zoom Meeting to reach participants from Sydney, Gold Coast, and Tamworth. The implementation method consisted of preparation, implementation, and evaluation stages. The training materials covered basic homiletical studies, biblical text interpretation, sermon structure development, illustration and application design, and communicative preaching delivery techniques. The training employed an andragogical-participatory model, positioning participants as active learners through discussion, reflection, and sermon-outline practice. The evaluation results indicated improvements in participants’ understanding, sermon preparation skills, and confidence in pulpit ministry. This activity positively contributed to strengthening the capacity of church ministers and was relevant to improving the quality of biblical proclamation within the context of Indonesian diaspora churches in Australia. The program also demonstrates the strategic role of theological institutions in empowering ecclesial ministry through applicable academic engagement. ABSTRAKKegiatan Pengabdian kepada Masyarakat ini bertujuan meningkatkan kompetensi homiletika pengkhotbah dan calon pengkhotbah GBI Miracle Service Australia melalui program training terstruktur. Kegiatan dilaksanakan secara daring melalui Zoom Meeting untuk menjangkau peserta dari Sydney, Gold Coast, dan Tamworth. Metode pelaksanaan mencakup tahap persiapan, pelaksanaan, dan evaluasi. Materi training meliputi kajian dasar homiletika, penafsiran teks Alkitab, penyusunan struktur khotbah, pengembangan ilustrasi dan aplikasi, serta teknik penyampaian khotbah yang komunikatif. Model pelatihan yang digunakan adalah andragogis-partisipatif, dengan menempatkan peserta sebagai subjek belajar yang aktif melalui diskusi, refleksi, dan latihan penyusunan kerangka khotbah. Hasil evaluasi menunjukkan adanya peningkatan pemahaman, keterampilan menyusun khotbah, dan kepercayaan diri peserta dalam pelayanan mimbar. Kegiatan ini berdampak positif terhadap penguatan kapasitas pelayan gereja serta relevan bagi pengembangan kualitas pemberitaan Firman Tuhan dalam konteks gereja diaspora Indonesia di Australia secara berkelanjutan dan kontekstual.